Preparation method of high-purity cobalt sulfate electrolyte for electrolytic cobalt

By crushing, dissolving the used ternary lithium battery and combining with the pretreatment and use of ion exchange resin, impurities and metals are adsorbed, and the problem of difficult removal of impurities such as Ni and Fe in the electrolyte solution for electrolytic cobalt in the prior art is solved, and the preparation of high-purity cobalt sulfate electrolyte is achieved.

CN119571395AInactive Publication Date: 2025-03-07YANGJIANG FEDERAL METAL CHEM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411752730.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove key impurities such as Ni and Fe in the electrolyte solution for electrolytic cobalt, making it difficult to prepare high-purity cobalt plates.

Method used

By crushing, dissolving, adding reducing agents and oxidizing agents for filtering and precipitation, combining the pretreatment and use of ion exchange resins, impurity metals are adsorbed, thereby preparing high-purity cobalt sulfate electrolyte.

Benefits of technology

It effectively reduces the presence of other metal impurities in the electrolyte, improves the leaching rate of cobalt and the oxidation and precipitation efficiency of impurity metals, and prepares a high-purity cobalt sulfate electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005165402220000091
    Figure BDA0005165402220000091
Patent Text Reader

Abstract

The invention relates to a preparation method of a high-purity cobaltous sulfate electrolyte for electrolyzing cobalt, and belongs to the technical field of electrolytes. The invention discloses a preparation method of a high-purity cobalt sulfate electrolyte for electrolytic cobalt, which specifically comprises the following steps: (1) crushing a waste ternary lithium battery to obtain battery powder; (2) adding water and sulfuric acid into the battery powder to obtain a dissolving solution; (3) adding a reducing agent into the dissolved solution, filtering, adding potassium permanganate and sodium chlorate into the filtrate, and filtering to obtain filtrate a; and (4) adsorbing impurities in the filtrate a by using ion exchange resin, wherein the adsorbed solution is the high-purity cobalt sulfate electrolyte. The high-purity cobaltous sulfate electrolyte is obtained by taking a waste ternary battery as a raw material and carrying out crushing, dissolving, reduction, oxidation precipitation and impurity removal by using ion exchange resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytes and relates to a method for preparing a high-purity cobalt sulfate electrolyte for electrolyzing cobalt. Background Art

[0002] High-purity metals play a vital role in the field of integrated circuits. In particular, my country has an urgent need for high-purity cobalt materials with a purity of more than 5N. High-purity cobalt targets for integrated circuits are key chip contact layer materials. Cobalt silicide gates based on self-aligned strained silicon technology can improve carrier mobility in the channel, reduce device impedance and power consumption, and improve drive current, frequency response and operating speed. They are key materials in large-scale integrated circuits with feature sizes above 90nm. With the development of semiconductor technology, high-purity cobalt targets for deep nano integrated circuit preparation have put forward more stringent requirements on the purity of cobalt raw materials, especially the most harmful key impurities Ni, Fe, Cu, etc. in large-scale integrated circuits. The limits of the above impurity elements in the domestic and foreign integrated circuit industries have been reduced to below ppm. Therefore, the difficulty in the preparation of high-purity cobalt is mainly to overcome the impurity removal technology of key impurities Ni, Fe, Cu and other elements. In the industry, the preparation method of high-purity cobalt mainly includes the preparation, purification, electrolysis and other processes of cobalt solution. Among them, solution purification is mainly used to remove metal impurities that are difficult to separate by electrochemical processes, such as Fe, Ni, Cu, etc. However, since the precipitation potential of these impurities is extremely close to that of cobalt at extremely low concentrations, the effect of purification by electrolysis is poor. The contents of Ni and Fe in the prepared electrolyte are both greater than 0.5 mg / L. In practical applications, it is difficult to prepare high-purity cobalt plates with such electrolytes. Therefore, the preparation technology of high-purity cobalt electrolytes still needs further exploration. Summary of the invention

[0003] The present invention relates to a method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt, and belongs to the technical field of electrolytes. The method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt disclosed in the present invention is as follows: (1) crushing waste ternary lithium batteries to obtain battery powder; (2) adding water and sulfuric acid to the battery powder to obtain a dissolving solution; (3) then adding a reducing agent to the dissolving solution, filtering, adding potassium permanganate and sodium chlorate to the filtrate, and filtering to obtain a filtrate a; (4) using an ion exchange resin to adsorb impurities in the filtrate a, and the solution after adsorption is a high-purity cobalt sulfate electrolyte. Using waste ternary batteries as raw materials, through crushing, dissolving, reducing, oxidative precipitation and using ion exchange resin to remove impurities, a high-purity cobalt sulfate electrolyte is obtained.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt, the method comprising the following steps:

[0006] (1) crushing the waste ternary lithium batteries to obtain battery powder;

[0007] (2) adding water and sulfuric acid to the battery powder and stirring to obtain a dissolved solution;

[0008] (3) then adding a reducing agent to the dissolved solution, mixing, filtering, first adding potassium permanganate to the filtrate, mixing, then heating, adding sodium chlorate, stirring, filtering, and obtaining a filtrate a;

[0009] (4) Using the pretreated ion exchange resin to adsorb the impurities in the filtrate a, the liquid after adsorption is a high-purity cobalt sulfate electrolyte.

[0010] Furthermore, in step (2), the mass ratio of battery powder, water and sulfuric acid is 3-4:5-10:3-5, and the stirring time and temperature are 1-1.5h and 60-70°C, respectively.

[0011] Furthermore, in the step (3), the amount of the reducing agent added to the dissolved solution is 20-30wt%, wherein the reducing agent is sodium sulfite, and the time and temperature for adding the reducing agent and mixing are 2-3h and 60-70°C, respectively.

[0012] Furthermore, in the step (3), the amounts of potassium permanganate and sodium chlorate added to the filtrate are 8-10wt% and 5-10wt% respectively, the time for adding potassium permanganate and mixing is 1.5h, the heating refers to heating to 80°C, and the time for adding sodium chlorate and stirring is 1h.

[0013] Furthermore, the specific steps of pre-treating the ion exchange resin in step (4) are: first soak the ion exchange resin in salt water, then use deionized water to wash until there is no other color on the surface, then soak it in sodium hydroxide solution, wash it with deionized water until it is neutral, and finally soak it in hydrochloric acid solution, wash it with deionized water until it is neutral, and then it is completed.

[0014] Furthermore, the volume ratio of the ion exchange resin to the brine is 1:2, wherein the mass concentration of the brine is 8-10%, the soaking time is 24 hours, and the brine solution is a sodium chloride solution.

[0015] Furthermore, the volumes of the sodium hydroxide solution and the hydrochloric acid solution are equal, wherein the mass concentration of the sodium hydroxide solution is 5-7%, and the immersion time in the sodium hydroxide solution is 24 hours.

[0016] Furthermore, the volumes of the hydrochloric acid solution and the brine are equal, wherein the mass concentration of the hydrochloric acid solution is 5-7%, and the immersion time in the hydrochloric acid solution is 24 hours.

[0017] Furthermore, in the step (4), the volume ratio of the pretreated ion exchange resin to the filtrate a is 1:2-3, and the adsorption time is 2-3h.

[0018] Beneficial effects of the present invention:

[0019] 1. Using sodium sulfite as a reducing agent effectively avoids the generation of gas that affects the operation, improves the leaching rate of cobalt, and effectively reduces the presence of other metal impurities in the filtrate. The addition of potassium permanganate and sodium chlorate improves the efficiency of impurity metals forming oxidative precipitation. At the same time, the pretreated ion exchange resin is used to adsorb the impurity metals to obtain a high-purity cobalt sulfate electrolyte. DETAILED DESCRIPTION

[0020] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.

[0021] Example 1

[0022] A method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt, the method comprising the following steps:

[0023] (1) crushing the waste ternary lithium batteries to obtain battery powder;

[0024] (2) adding water and sulfuric acid to the battery powder and stirring to obtain a dissolved solution;

[0025] (3) then adding a reducing agent to the dissolved solution, mixing, filtering, first adding potassium permanganate to the filtrate, mixing, then heating, adding sodium chlorate, stirring, filtering, and obtaining a filtrate a;

[0026] (4) Using the pretreated ion exchange resin to adsorb the impurities in the filtrate a, the liquid after adsorption is a high-purity cobalt sulfate electrolyte.

[0027] The mass ratio of battery powder, water and sulfuric acid in step (2) is 3:5:3, and the stirring time and temperature are 1 hour and 60° C. respectively.

[0028] In the step (3), the amount of the reducing agent added to the dissolving solution is 20 wt %, wherein the reducing agent is sodium sulfite, and the time and temperature for adding the reducing agent and mixing are 2 h and 60° C. respectively.

[0029] In the step (3), the amounts of potassium permanganate and sodium chlorate added to the filtrate are 8wt% and 5wt% respectively, the time for adding potassium permanganate and mixing is 1.5h, the heating refers to heating to 80°C, and the time for adding sodium chlorate and stirring is 1h.

[0030] The specific steps of pre-treating the ion exchange resin in step (4) are: first soak the ion exchange resin in salt water, then use deionized water to wash until there is no other color on the surface, then soak it in sodium hydroxide solution, wash it with deionized water until it is neutral, and finally soak it in hydrochloric acid solution, wash it with deionized water until it is neutral, and then it is completed.

[0031] The volume ratio of the ion exchange resin to the brine is 1:2, wherein the mass concentration of the brine is 8%, the soaking time is 24 hours, and the brine solution is a sodium chloride solution.

[0032] The volumes of the sodium hydroxide solution and the hydrochloric acid solution are equal, wherein the mass concentration of the sodium hydroxide solution is 5%, and the immersion time in the sodium hydroxide solution is 24 hours.

[0033] The volumes of the hydrochloric acid solution and the salt water are equal, wherein the mass concentration of the hydrochloric acid solution is 5%, and the immersion time in the hydrochloric acid solution is 24 hours.

[0034] In the step (4), the volume ratio of the pretreated ion exchange resin to the filtrate a is 1:2, and the adsorption time is 2 hours.

[0035] The model of the ion exchange resin is 001×7 macroporous strongly acidic cation exchange resin.

[0036] Example 2

[0037] A method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt, the method comprising the following steps:

[0038] (1) crushing the waste ternary lithium batteries to obtain battery powder;

[0039] (2) adding water and sulfuric acid to the battery powder and stirring to obtain a dissolved solution;

[0040] (3) then adding a reducing agent to the dissolved solution, mixing, filtering, first adding potassium permanganate to the filtrate, mixing, then heating, adding sodium chlorate, stirring, filtering, and obtaining a filtrate a;

[0041] (4) Using the pretreated ion exchange resin to adsorb the impurities in the filtrate a, the liquid after adsorption is a high-purity cobalt sulfate electrolyte.

[0042] The mass ratio of battery powder, water and sulfuric acid in step (2) is 3.5:7.5:4, and the stirring time and temperature are 1.2 h and 65° C. respectively.

[0043] In the step (3), the amount of the reducing agent added to the dissolving solution is 25 wt %, wherein the reducing agent is sodium sulfite, and the time and temperature for adding the reducing agent and mixing are 2.5 h and 65° C. respectively.

[0044] In the step (3), the amounts of potassium permanganate and sodium chlorate added to the filtrate are 9wt% and 7.5wt% respectively, the time for adding potassium permanganate and mixing is 1.5h, the heating refers to heating to 80°C, and the time for adding sodium chlorate and stirring is 1h.

[0045] The specific steps of pre-treating the ion exchange resin in step (4) are: first soak the ion exchange resin in salt water, then use deionized water to wash until there is no other color on the surface, then soak it in sodium hydroxide solution, wash it with deionized water until it is neutral, and finally soak it in hydrochloric acid solution, wash it with deionized water until it is neutral, and then it is completed.

[0046] The volume ratio of the ion exchange resin to the brine is 1:2, wherein the mass concentration of the brine is 8-10%, the soaking time is 24 hours, and the brine solution is a sodium chloride solution.

[0047] The volumes of the sodium hydroxide solution and the hydrochloric acid solution are equal, wherein the mass concentration of the sodium hydroxide solution is 6%, and the immersion time in the sodium hydroxide solution is 24 hours.

[0048] The volumes of the hydrochloric acid solution and the brine are equal, wherein the mass concentration of the hydrochloric acid solution is 6%, and the immersion time in the hydrochloric acid solution is 24 hours.

[0049] The volume ratio of the pretreated ion exchange resin to the filtrate a in step (4) is 1:2.5, and the adsorption time is 2.5 hours.

[0050] The model of the ion exchange resin is 001×7 macroporous strongly acidic cation exchange resin.

[0051] Example 3

[0052] A method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt, the method comprising the following steps:

[0053] (1) crushing the waste ternary lithium batteries to obtain battery powder;

[0054] (2) adding water and sulfuric acid to the battery powder and stirring to obtain a dissolved solution;

[0055] (3) then adding a reducing agent to the dissolved solution, mixing, filtering, first adding potassium permanganate to the filtrate, mixing, then heating, adding sodium chlorate, stirring, filtering, and obtaining a filtrate a;

[0056] (4) Using the pretreated ion exchange resin to adsorb the impurities in the filtrate a, the liquid after adsorption is a high-purity cobalt sulfate electrolyte.

[0057] The mass ratio of battery powder, water and sulfuric acid in step (2) is 4:10:5, and the stirring time and temperature are 1.5h and 70°C respectively.

[0058] In the step (3), the amount of the reducing agent added to the dissolving solution is 30 wt %, wherein the reducing agent is sodium sulfite, and the time and temperature for adding the reducing agent and mixing are 3 h and 70° C. respectively.

[0059] In the step (3), the amounts of potassium permanganate and sodium chlorate added to the filtrate are 10 wt% and 10 wt% respectively, the time for adding potassium permanganate and mixing is 1.5 h, the heating refers to heating to 80° C., and the time for adding sodium chlorate and stirring is 1 h.

[0060] The specific steps of pre-treating the ion exchange resin in step (4) are: first soak the ion exchange resin in salt water, then use deionized water to wash until there is no other color on the surface, then soak it in sodium hydroxide solution, wash it with deionized water until it is neutral, and finally soak it in hydrochloric acid solution, wash it with deionized water until it is neutral, and then it is completed.

[0061] The volume ratio of the ion exchange resin to the brine is 1:2, wherein the mass concentration of the brine is 10%, the soaking time is 24 hours, and the brine solution is a sodium chloride solution.

[0062] The volumes of the sodium hydroxide solution and the hydrochloric acid solution are equal, wherein the mass concentration of the sodium hydroxide solution is 7%, and the immersion time in the sodium hydroxide solution is 24 hours.

[0063] The volumes of the hydrochloric acid solution and the brine are equal, wherein the mass concentration of the hydrochloric acid solution is 7%, and the immersion time in the hydrochloric acid solution is 24 hours.

[0064] The volume ratio of the pretreated ion exchange resin to the filtrate a in step (4) is 1:3, and the adsorption time is 3 hours.

[0065] The model of the ion exchange resin is 001×7 macroporous strongly acidic cation exchange resin.

[0066] Comparative Example 1

[0067] On the basis of Example 3, a method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt is provided, wherein the method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt comprises the following steps:

[0068] (1) crushing the waste ternary lithium batteries to obtain battery powder;

[0069] (2) adding water and sulfuric acid to the battery powder and stirring to obtain a dissolved solution;

[0070] (3) then adding a reducing agent to the dissolved solution, mixing, filtering, first adding potassium permanganate to the filtrate, mixing, then heating, adding sodium chlorate, stirring, filtering, and obtaining a filtrate a;

[0071] (4) Using the pretreated ion exchange resin to adsorb the impurities in the filtrate a, the liquid after adsorption is a high-purity cobalt sulfate electrolyte.

[0072] The mass ratio of battery powder, water and sulfuric acid in step (2) is 4:10:5, and the stirring time and temperature are 1.5h and 70°C respectively.

[0073] In the step (3), the amount of the reducing agent added to the dissolving solution is 30 wt %, wherein the reducing agent is sodium chloride, and the time and temperature for adding the reducing agent and mixing are 3 h and 70° C. respectively.

[0074] In the step (3), the amounts of potassium permanganate and sodium chlorate added to the filtrate are 10 wt% and 10 wt% respectively, the time for adding potassium permanganate and mixing is 1.5 h, the heating refers to heating to 80° C., and the time for adding sodium chlorate and stirring is 1 h.

[0075] The specific steps of pre-treating the ion exchange resin in step (4) are: first soak the ion exchange resin in salt water, then use deionized water to wash until there is no other color on the surface, then soak it in sodium hydroxide solution, wash it with deionized water until it is neutral, and finally soak it in hydrochloric acid solution, wash it with deionized water until it is neutral, and then it is completed.

[0076] The volume ratio of the ion exchange resin to the brine is 1:2, wherein the mass concentration of the brine is 10%, the soaking time is 24 hours, and the brine solution is a sodium chloride solution.

[0077] The volumes of the sodium hydroxide solution and the hydrochloric acid solution are equal, wherein the mass concentration of the sodium hydroxide solution is 7%, and the immersion time in the sodium hydroxide solution is 24 hours.

[0078] The volumes of the hydrochloric acid solution and the brine are equal, wherein the mass concentration of the hydrochloric acid solution is 7%, and the immersion time in the hydrochloric acid solution is 24 hours.

[0079] The volume ratio of the pretreated ion exchange resin to the filtrate a in step (4) is 1:3, and the adsorption time is 3 hours.

[0080] The model of the ion exchange resin is 001×7 macroporous strongly acidic cation exchange resin.

[0081] Comparative Example 2

[0082] On the basis of Example 3, a method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt is provided, wherein the method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt comprises the following steps:

[0083] (1) crushing the waste ternary lithium batteries to obtain battery powder;

[0084] (2) adding water and sulfuric acid to the battery powder and stirring to obtain a dissolved solution;

[0085] (3) then adding a reducing agent to the dissolved solution, mixing, filtering, first adding potassium permanganate to the filtrate, mixing, then heating, adding sodium chlorate, stirring, filtering, and obtaining a filtrate a;

[0086] (4) A metal extractant is added to the filtrate a for extraction, and the raffinate after separation is a high-purity cobalt sulfate electrolyte.

[0087] The mass ratio of battery powder, water and sulfuric acid in step (2) is 4:10:5, and the stirring time and temperature are 1.5h and 70°C respectively.

[0088] In the step (3), the amount of the reducing agent added to the dissolving solution is 30 wt %, wherein the reducing agent is sodium sulfite, and the time and temperature for adding the reducing agent and mixing are 3 h and 70° C. respectively.

[0089] In the step (3), the amounts of potassium permanganate and sodium chlorate added to the filtrate are 10 wt% and 10 wt% respectively, the time for adding potassium permanganate and mixing is 1.5 h, the heating refers to heating to 80° C., and the time for adding sodium chlorate and stirring is 1 h.

[0090] In the step (4), the volume ratio of the filtrate a to the metal extractant is 1:1, wherein the metal extractant is di-(2-ethylhexyl)phosphoric acid.

[0091] Comparative Example 3

[0092] On the basis of Example 3, the addition of potassium permanganate in step (3) was removed, and the other conditions were the same as those in Example 3.

[0093] Comparative Example 4

[0094] On the basis of Example 3, the sodium chlorate in step (3) was removed, and the other conditions were consistent with those in Example 3.

[0095] 1. Performance Testing

[0096] The high-purity cobalt sulfate electrolyte prepared in Example 3 and Comparative Examples 1-4 was evaporated and concentrated to form crystals and sampled for chemical analysis.

[0097] The above test results are shown in Table 1:

[0098] Table 1 Chemical composition analysis and content (w / %)

[0099]

[0100] As can be seen from Table 1, the cobalt content of Example 3 is the largest, and the remaining contents of other metal elements are also relatively small. The cobalt content in Comparative Example 1 is relatively small, and the contents of Ni, Fe, and Mg are significantly increased. Since the reducing agent in Comparative Example 1 is sodium chloride, the leaching efficiency of cobalt is reduced, and the generation of chlorine affects the reaction process; Comparative Example 2 uses an ion exchange resin adsorption process instead of an extraction process, and the degree of separation of the extraction is lower than the adsorption of the resin; Comparative Examples 3-4 add an oxidant, whose oxidation efficiency decreases, so that the impurity metal ions do not form precipitation, and then the doping of a higher content of impurities affects the purity of cobalt sulfate.

[0101] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a high-purity cobalt sulfate electrolyte for electrolytic cobalt, characterized in that: The method for preparing a high-purity cobalt sulfate electrolyte for electrolytic cobalt comprises the following steps: (1) crushing the waste ternary lithium batteries to obtain battery powder; (2) adding water and sulfuric acid to the battery powder and stirring to obtain a dissolved solution; (3) then adding a reducing agent to the dissolved solution, mixing, filtering, first adding potassium permanganate to the filtrate, mixing, then heating, adding sodium chlorate, stirring, filtering, and obtaining a filtrate a; (4) Using the pretreated ion exchange resin to adsorb the impurities in the filtrate a, the liquid after adsorption is a high-purity cobalt sulfate electrolyte.

2. The method for preparing a high-purity cobalt sulfate electrolyte for electrolytic cobalt according to claim 1, characterized in that: The mass ratio of battery powder, water and sulfuric acid in step (2) is 3-4:5-10:3-5, and the stirring time and temperature are 1-1.5h and 60-70°C respectively.

3. The method for preparing a high-purity cobalt sulfate electrolyte for electrolytic cobalt according to claim 1, characterized in that: In the step (3), the amount of the reducing agent added to the dissolving solution is 20-30wt%, wherein the reducing agent is sodium sulfite, and the time and temperature for adding the reducing agent and mixing are 2-3h and 60-70°C, respectively.

4. The method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt according to claim 1, characterized in that: In the step (3), the amounts of potassium permanganate and sodium chlorate added to the filtrate are 8-10wt% and 5-10wt%, respectively. The time for adding potassium permanganate and mixing is 1.5h. The heating refers to heating to 80°C. The time for adding sodium chlorate and stirring is 1h.

5. The method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt according to claim 1, characterized in that: The specific steps of pre-treating the ion exchange resin in step (4) are: first soak the ion exchange resin in salt water, then wash it with deionized water until there is no other color on the surface, then soak it in sodium hydroxide solution, wash it with deionized water until it is neutral, and finally soak it in hydrochloric acid solution, wash it with deionized water until it is neutral, and then it is completed.

6. The method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt according to claim 5, characterized in that: The volume ratio of the ion exchange resin to the brine is 1:2, wherein the mass concentration of the brine is 8-10%, the soaking time is 24 hours, and the brine solution is a sodium chloride solution.

7. The method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt according to claim 5, characterized in that: The volumes of the sodium hydroxide solution and the hydrochloric acid solution are equal, wherein the mass concentration of the sodium hydroxide solution is 5-7%, and the soaking time in the sodium hydroxide solution is 24 hours.

8. The method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt according to claim 5, characterized in that: The volumes of the hydrochloric acid solution and the salt water are equal, wherein the mass concentration of the hydrochloric acid solution is 5-7%, and the immersion time in the hydrochloric acid solution is 24 hours.

9. The method for preparing a high-purity cobalt sulfate electrolyte for electrolysis of cobalt according to claim 1, characterized in that: In the step (4), the volume ratio of the pretreated ion exchange resin to the filtrate a is 1:2-3, and the adsorption time is 2-3h.

Citation Information

Patent Citations

  • Method for treating cobalt-nickel-copper hydrometallurgy wastewater residue

    CN102925706A

  • Step-by-step leaching method of nickel and cobalt from mixture of nickel, cobalt and manganese

    CN109868373A

  • Preparation method of cobalt sulfate electrolyte for ultra-pure cobalt

    CN115627499A